The effects of uncertainty on market liquidity: Evidence from Hurricane Sandy - Dominik Rehse; Ryan Riordan; Nico Rottke; Joachim Zietz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We test the effects of uncertainty on market liquidity using Hurricane Sandy as a natural experiment. Given the unprecedented strength, scale and nature of the storm, the potential damages of a landfall near the Greater New York area were unpredictable and therefore uncertain. Using a difference-in-differences setting, we compare the market reactions of Real Estate Investment Trusts (REITs) with and without properties in the widely-published evacuation zone of New York City prior to landfall. We nd relatively less trading and wider bid-ask spreads in affected REITs. The results confirm theory on the detrimental effects of uncertainty on market functioning.
urn:nbn:de:bsz:180-madoc-461619
Keywords: G12; G14; 330; Uncertainty; liquidity; financial crisis; natural experiment